Poly- and Perfluoroalkyl Substances (PFAS) in Landfills: Occurrence, Transformation and Treatment. (1st January 2023) - Zhang, Man; Zhao, Xianda; Zhao, Dongye; Soong, Te-Yang; Tian, Shuting
Graphical abstract: Highlights: C4-C7 PFCAs are predominant in leachate, while FOTHs are dominant in landfill air. The quality of installed landfill liners is critical for minimizing PFAS leakage. Activated carbon, ion exchange, and reverse osmosis are effective for treating PFAS in leachate. Foam fractionation and advanced oxidation are effective per laboratory/pilot scale tests. Key knowledge gaps in PFAS management at landfills are identified. Abstract: Landfills have served as the final repository for > 50 % municipal solid wastes in the United States. Because of their widespread uses and persistence in the environment, per- and polyfluoroalkyl substances (PFAS) (>4000 on the global market) are ubiquitously present in everyday consumer, commercial and industrial products, and have been widely detected in both closed (tens ng/L) and active (thousands to ten thousands ng/L) landfills due to disposal of PFAS-containing materials. Along with the decomposition of wastes in-place, PFAS can be transformed and released from the wastes into leachate and landfill gas. Consequently, it is critical to understand the occurrence and transformation of PFAS in landfills and the effectiveness of landfills, as a disposal alternative, for long-term containment of PFAS. This article presents a state-of-the-art review on the occurrence and transformation of PFAS in landfills, and possible effect of PFAS on the integrity of modern liner systems. Based on the data published from 10 countries (250 + landfills), C4-C7 perfluoroalkyl carboxylic acids were found predominant in the untreated landfill leachate and neutral PFAS, primarily fluorotelomer alcohols, in landfill air. The effectiveness and limitations of the conventional leachate treatment technologies and emerging technologies were also evaluated to address PFAS released into the leachate. Among conventional technologies, reverse osmosis (RO) may achieve a high removal efficiency of 90–100 % based on full-scale data, which, however, is vulnerable to the organic fouling and requires additional disposal of the concentrate. Implications of these knowledge on PFAS management at landfills are discussed and major knowledge gaps are identified.